Fluorescent polystyrene microbeads as invisible security ink and optical vapor sensor for 4-nitrotoluene - Sonawane, Swapnil L.; Asha, S. K. (ACS Applied Materials & Interfaces, 2016)
Color-tunable solid-state emitting polystyrene (PS) microbeads were developed by dispersion polymerization, which showed excellent fluorescent security ink characteristics along with sensitive detection of vapors of nitro aromatics like 4 nitro toluene (4-NT). The fluorophores pyrene and perylenebisimide were incorporated into the PS backbone as acrylate monomer and acrylate cross-linker, respectively. Solid state quantum yields of 94 and 20% were observed for the pyrene and perylenebisimide, respectively, in the PS/Py and PS/PBI polymers. The morphology and solid state fluorescence was measured by SEM, fluorescence microscopy, and absorbance and fluorescence spectroscopy techniques. The ethanol dispersion of the polymer could be used directly as a fluorescent security ``invisible'' ink, which became visible only under ultraviolet light. The color of the ink could be tuned depending on the amounts of the pyrene and perylenebisimide incorporated with blue and orange-green for pyrene alone or perylenebisimide alone beads respectively and various shades in between including pure white for beads incorporating both the fluorophores. More than 80% quenching of pyrene emission was observed upon exposure of the polymer in the form of powder or as spin-coated films to the vapors of 4-NT while the emission of perylenebisimide was unaffected. The limit of detection was estimated at 10(-5) moles (2.7 ppm) of 4-NT vapors. The ease of synthesis of the material along with its invisible ink characteristics and nitro aromatic vapor detection opens up new opportunities for exploring the application of these PS-based materials as optical sensors and fluorescent ink for security purposes.
Keywords: dispersion polymerization; invisible security ink; Perylenebisimide; pyrene; solid state detection